Is the Cloze Procedure Appropriate to Evaluate Health Literacy in Older Individuals? Age Effects in the Test of Functional Health Literacy in Adults - Raymond L. Ownby; Amarilis Acevedo; Drenna Waldrop-Valverde; Robin J. Jacobs (Journal of Aging Research)
Health literacy has received increasing attention because of its importance for older individuals’ health, as studies have shown a close relation between older individuals’ health literacy and their health. Research also suggests that older individuals have low levels of health literacy, but this finding is variable and may depend on which health literacy test is used. Older individuals assessed with the Test of Functional Health Literacy (TOFHLA) score lower than younger individuals, but a previous study suggested that this may result from age-related differential item functioning (DIF) on the TOFHLA. The study reported here assessed age-related DIF in a sample of community-dwelling volunteers. Twenty-two percent of items were differentially more difficult for older individuals independent of their overall ability, and when these items were eliminated from the total score, age differences were no longer found. Performance on a working memory task predicted older but not younger individuals’ performance on the age-related items. At least part of older individuals’ apparent deficits in health literacy when assessed by the TOFHLA may be related to DIF on its items. The TOFHLA, and any measure that employs the cloze procedure to evaluate reading comprehension, should be used cautiously in older individuals.